LncRNA HOTAIR is a Prognostic Biomarker for the Proliferation and Chemoresistance of Colorectal Cancer via MiR-203a-3p-Mediated Wnt/ß-Catenin Signaling Pathway - Zhigang Xiao; Zhan Qu; Zhikang Chen; Zhixue Fang; Ke Zhou; Zhongcheng Huang; Xiong Guo; Yang Zhang (Cellular Physiology and Biochemistry, 2018)
Background/Aims: HOX transcript antisense RNA (HOTAIR) plays a vital role in carcinogenesis. However, its functional and regulatory roles remain unclear. In this study, we aimed to investigate its biological function and clinical significance in human colorectal cancer (CRC). Methods: We examined the expression levels of lncRNA HOTAIR and miR-203a-3p in CRC tissues and CRC cell lines by qRT-PCR. Gain and loss-of-function assays were performed to examine the effects of HOTAIR and miR-203a-3p on the proliferation and chemoresistance of CRC cells. The possible mechanisms of HOTAIR were also explored by fluorescence reporter assay and Western blot. Results: The expressions of HOTAIR were upregulated in CRC tissue tissues compared to adjacent control tissues. We also found HOTAIR was downregulated by miR-203a-3p in CRC cell lines. Both HOTAIR knockdown and miR-203a-3p overexpression in CRC cell lines led to inhibited cell proliferation and reduced chemoresistance. We also determined that β-catenin and GRG5 were inhibitory targets of miR-203a-3p, and that Wnt/β-catenin signaling was inhibited by both HOTAIR knockdown and miR-203a-3p overexpression. Significantly, we found that increased expression of miR-203a-3p is essential for cell proliferation repression, chemoresistance reduction, and Wnt/β-catenin signaling inhibition induced by HOTAIR knockdown. Conclusions: Our study demonstrated that the lncRNA HOTAIR could regulate the progression and chemoresistance of CRC via modulating the expression levels of miR-203a-3p and the activity of Wnt/β-catenin signaling pathway.